SUSCEPTIBILITY OF MICROBIAL INFECTIOUS AGENTS TO THE LATEX AND LEAF EXTRACT OF Calotropis procera - IBRAHIM, H. I.; HAMZA, A. J.; SALAWUDEEN, A.; UMMU, R. A.; HANIFA, M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The age-old traditional usage of the Calotropis procera plant for the treatment of several infectious diseases has established the plant as ethnomedicinal with widely reported exploitation in current herbal medicinal practice. This prompted the investigation of the in vitro susceptibility of various disease-causing microorganisms to various doses of the latex and leaf extract of the C. procera plant. The latex and leaves of the C. procera plant were collected and processed before subjecting the leaf to ethanol extraction via the maceration protocol. The various concentrations of the latex and leaf extract of C. procera were subjected to antimicrobial susceptibility tests using the agar well diffusion technique. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined according to standard microbiological methods. The C. procera latex exhibited antimicrobial activity against microbial isolates even at the lowest concentration of 20 % (v/v) except for E. coli which was not susceptible at this concentration. Lower antimicrobial activity was observed with the leaf extract of C. procera even though antifungal activity against C. albican was high with both the latex and the leaf extract. The MIC of the C. procera latex detected at 12.5 and 25 % (v/v) and MBC at quarter strength of the latex also emphasized the inhibitory and bactericidal capability of the C. procera latex against bacterial infectious agents of clinical origin. The study attributed the antimicrobial potency of the C. procera latex and leaf extract to its phytochemicals as widely referred in the literature. As per findings from this study, C. procera could serve as a valuable pharmacological prospect for the development of new natural antimicrobial drugs from plant sources that could be useful in combating today's menace of antibiotic resistance.